PLAUSIBLE IMPACTS OF CLIMATE CHANGE ON POTATO IN SOME IMPORTANT POTATO GROWING POCKETS IN INDIA BASED ON INFERENCE FROM THEIR CLIMATE ANALOGUES - Govindakrishnan, PM; Singh, Bir Pal; Sharma, Samiksha; Rawat, Shashi (Potato Journal, 2016)
Scientific evidence gathered over the last couple of decades suggests that climatic conditions are changing rapidly. This trend is likely to continue, and even accelerate in future (IPCC 2007; Moss et al., 2010). These anticipated changes in climate baseline, variability, and extremes will have far-reaching consequences on agricultural production, posing additional challenges to meeting the food security for a growing world population (Lobell et al., 2008; Roudier et al., 2011). It is therefore pertinent to work out the impact of climate change on agricultural production, and develop, both mitigation and adaptation strategies. Although various methods have been proposed for the purpose but climate analogues offer a simple alternative. Reason being that relying on â€œanalogue locationsâ€ that have today the climatic characteristics that are expected tomorrow in a target production zone can help predict the effect of changing climate on crops (Haussmann et al., 2012). Moreover, such studies are more realistic, since, in addition to crop growth and development the pests and diseases complex can also be studied. This study was therefore undertaken to determine the climate analogues of important potato growing regions to assess the possible impact of climate change in future.